Assessing freedom of movement for counterinsurgency campaigns - Connable, Ben.; Campbell, Jason H.; Loidolt, Bryce; Fisher, Gail.; National Defense Research Institute (U.S.).; International Security and Defense Policy Center; Rand Corporation; United States Forces, Afghanistan; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2012)
Freedom of movement (FoM) is the actual or perceived degree to which individuals or groups can move from place to place within a given environment or into and out of that environment. FoM is clearly an important consideration in the development of counterinsurgency tactics, operations, and strategies, but it is addressed infrequently and inconsistently in the doctrine and literature on counterinsurgency. A consistent, comprehensive definition of FoM must take into account the range of complexities and challenges posed by the operating environment, as well as the practical reality that FoM means something different to different groups. Focusing specifically on Afghanistan, this examination considers actual and perceived FoM for civilians, coalition and Afghan security forces, government officials, nongovernmental organizations, and insurgents and profiles the factors that influence these groups and affect data reporting in potentially misleading ways. It also serves as a guide for a bottom-up approach to developing sustainable FoM assessment processes that consider the range of variables that can enable and inhibit actual freedom to move and that can affect the subsequent analysis of FoM data. A historical and global review of a sample of the FoM assessment literature and interviews with assessment experts also clarify best practices and gaps in knowledge and capability that assessment staffs could address.
"RAND National Defense Research Institute."
Introduction -- How the Concept of Freedom of Movement Can Inform Assessment -- Analysis of Past and Current Theory and Practice -- Recommendations.
Includes bibliographical references (p. 59-70).
Also available on the internet via WWW in PDF format.
Keywords: Counterinsurgency -- Afghanistan; Military planning -- United States; Afghanistan -- Politics and government -- 2001-